Correlation between Nutritional Status of Mothers During Pregnancy and Stunting Incidence at the Age of 24-59 Months at Godean Health Center 1 - Yeyen Kurnia; Ismarwati Ismarwati (Jurnal Kebidanan, 2023)
The prevalence of stunting under-fives in Indonesia is still high, namely 29.6%. The 2014 Global Nutrition Report showed that Indonesia was included in 17 countries, among 117 countries, which had three nutritional problems, namely stunting, wasting and overweight in under-fives. Mothers who experience malnutrition are at risk of giving birth to malnourished babies. Fetuses that are malnourished from the womb are at greater risk of being born stunted. The impact of stunting is having a level of intelligence that is not optimal, making children more susceptible to disease and in the future there may be a risk of declining levels of productivity. This study aims to determine the correlation between mother's nutritional status during pregnancy and the incidence of stunting at the age of 24-59 months at Godean I Primary Health Center. The design of this study was case control using a retrospective approach. The number of samples was 92 respondents with a comparison of case groups and control groups 1: 1 taken at Godean 1 Primary Health Center with random sampling technique. The data analysis used Fisher Exact Test. The results of this study showed that there was a significant correlation between mother's nutritional status during pregnancy and the incidence of stunting at the age of 24-59 months with a value of 0.005 (<0.05), the Contingency Coefficient value of 0.302 indicating a low level of correlation closeness. Mothers are expected to pay attention to nutritional status during pregnancy in order to prevent the incidence of stunting in children.